Climate change pressure on yields by 2050: Africa and South Asia in particular - CGIAR Research Program on Wheat (2021)
Most negative impacts are projected to affect developing countries in tropical regions: Model ensemble mean suggests large negative yield impacts for African (−15%) and Southern Asian countries (−16%) by 2050.